Prestate of Stress and Fault Behavior During the 2016 Kumamoto Earthquake (M7.3). Issue 2 (18th January 2018) - Matsumoto, Satoshi; Yamashita, Yusuke; Nakamoto, Manami; Miyazaki, Masahiro; Sakai, Shinichi; Iio, Yoshihisa; Shimizu, Hiroshi; Goto, Kazuhiko; Okada, Tomomi; Ohzono, Mako; Terakawa, Toshiko; Kosuga, Masahiro; et al.
Abstract: Fault behavior during an earthquake is controlled by the state of stress on the fault. Complex coseismic fault slip on large earthquake faults has recently been observed by dense seismic networks, which complicates strong motion evaluations for potential faults. Here we show the three‐dimensional prestress field related to the 2016 Kumamoto earthquake. The estimated stress field reveals a spatially variable state of stress that forced the fault to slip in a direction predicted by the "Wallace and Bott Hypothesis." The stress field also exposes the pre‐condition of pore fluid pressure on the fault. Large coseismic slip occurred in the low‐pressure part of the fault. However, areas with highly pressured fluid also showed large displacement, indicating that the seismic moment of the earthquake was magnified by fluid pressure. These prerupture data could contribute to improved seismic hazard evaluations. Plain Language Summary: The three‐dimensional prestress field around the 2016 Kumamoto earthquake controlled fault behavior of the earthquake. The estimated heterogeneous state of stress on the fault forced the fault to slip in the direction predicted. The stress field also exposed the precondition of pore fluid pressure on the fault. Large coseismic slip occurred not only at the low‐pressure part of the fault but also highly pressured part. It indicates that the seismic moment of the earthquake was magnified by fluid pressure. These prerupture data could contribute to upgrading seismic hazard evaluation. Key Points: A heterogeneous stress field is detected at the 2016 Kumamoto earthquake hypocentral area The expected slip direction from the estimated stress field correlates with the coseismic slip Highly pressured fluids around the fault enlarged the coseismic slip of the main shock